The career costs of children - Jérôme Adda; Christian Dustmann; Katrien Stevens (Institute for the Study of Labor (IZA), 2011)
This paper analyzes the life-cycle career costs associated with child rearing and decomposes their effects into unearned wages (as women drop out of the labor market), loss of human capital, and selection into more child-friendly occupations. We estimate a dynamic life-cycle model of fertility, occupational choice, and labor supply using detailed survey and administrative data for Germany for numerous birth cohorts across different regions. We use this model to analyze both the male-female wage gap as it evolves from labor market entry onward and the effect of pro-fertility policies. We show that a substantial portion of the gender wage gap is explainable by realized and expected fertility and that the long-run effect of policies encouraging fertility are considerably lower than the short-run effects typically estimated in the literature.
urn:nbn:de:101:1-201201107504
Keywords: J1; J2; J31; 330; fertility; labor supply; occupational choice; Familienplanung; Kinder; Frauen; Karriereplanung; Arbeitsangebot; Einkommen; Geschlechterdiskriminierung; Theorie